Passing : a memoir of love and death - Korda, Michael, 1933- (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2019)
"In the tradition of The Year of Magical Thinking comes a legendary editor's unflinching love song about his radiant wife, Margaret, and her battle with cancer. It was a warm April in Pleasant Valley when Margaret Korda, normally a fearless horsewoman, dropped her horsewhip while she was riding. Such a mild slip was easy to ignore, but when other troubling symptoms accumulated, she confided to her husband, 'Michael, I think something serious is wrong with me.' Within a few rapid weeks, the fiercely independent, former fashion model was diagnosed with brain cancer, while Michael, once reliant on her steeliness, became her caregiver, deciphering bewildering medical reports and packing her beloved toiletries for the hospital. An operation performed by a renowned surgeon allowed Margaret to ride her favorite competition horse Logan go Bragh a few more times, but Margaret's tumors quickly returned-leaving her to grapple with the reality of impending death. In rapturous prose, Korda, a modern- day Orpheus, braids her heroic story with heartrending details of their final year together. Passing, a tender memoir, is a testament to the transcendent possibilities of love"--